The influence of nitrogen admixture on concentration of an electronic–excited helium atoms in atmospheric pressure glow discharge - Arkhipenko, V.I.; Kirillov, A.A.; Simonchik, L.V.; Zgirouski, S.M. (Вопросы атомной науки и техники, 2005)
The concentrations of the low-excited helium atoms in states 2¹S, 2¹P, 2³S and 2³P were determined in the atmospheric pressure glow discharge in helium (99.98%He) and in helium with a nitrogen admixture (99.5%He + 0.5%N2). It was shown that the adding of nitrogen into helium leads to the drastically reduction of concentration of both the low-excited helium atoms and ions.